Academician profile system for developing an ICT academic community - Abdul Rahman, Azra Ayue (2005)
This project tackles the following problems: first, there is no clear identification on profile features and type of search that support retrieval of profile to provide information that help manage academic activities in ICT Academic Community; secondly there is no apparent identification on communication tools that allow interaction and information exchange to encourage affiliation among Community of Practice (CoP) in ICT Academic Community and thirdly, there is no particular profile system that been developed (based on the proposed profile features, type of search and communication tools) that enables retrieval of profile together with interaction and information exchange towards ICT Academic Community development. The main findings of the study are the sixteen main academician profile features (Personal Data, Education/Qualification, Expertise/Specialization, Work Experience, Administrative Experience, Teaching Experience, Thesis/Dissertation/Report Examiner Experience, Supervision Experience, Research Experience, Consultancy Experience, Committee Experience, Compile Editorial Experience, Publication/Writing Experience, Academic Voluntary Service, Membership in Association, and Awards/ Recognition) and type of search (the category searches and free text searches). The proposed communication tools, consists of Community Membership, Information Resources, Interaction Facilities and Additional components contributed by the community members. These findings were incorporated in the form of a prototype web-based Academician Profile System. The system was developed using PHP, Macromedia Dreamweaver MX, Apache, MySQL and Rational Rose. The prototype was tested using the User Acceptance Test with ten ICT academician that shows it supports retrieval of profile that provide information to help manage academic activities as well as allows interaction and information exchange for ICT Academic Community development